Josep M. Figueres i Artigues (2013): La veu de Catalunya - Hernández López, Jóse Miguel (RIHC. Revista Internacional de Historia de la Comunicación, 2015)
La Veu de Catalunya Josep Maria Figueres i Artigues Editorial Base, Barcelona, 2013 693 pp.